TUNTUTAN MASYARAKAT TERHADAP KELUARNYA TURKI DARI KONVENSI ISTANBUL - Femri Resdifianti; Dini Septianti Nurkhasanah; Ratih Kusuma Dewi (Indonesian Journal of International Relations, 2022)
On March 20, 2021, Turkey withdrew from the Istanbul Convention, a human rights treaty against violence against women and domestic violence. The decision was inseparable from the demands of the Turkish people in the public sphere, who intensively lobbied the Turkish government to reject and withdraw from the Istanbul Convention. This article aims to analyze the influence of Turkish public demands on Turkey's decision to leave the Istanbul Convention using Habermas' public sphere theory. The author first describes Turkey's anti-gender discourse and movement. This anti-gender movement is backed by a pro-Islamic and traditional pro-gender ruling government. President Erdogan even expressed his disapproval of the feminist movement and the concept of gender equality. In addition, the author also describes the political background in Turkey's exit from the Istanbul Convention. The writing method uses a descriptive qualitative approach with a literature review technique. The result of this research is that the Turkish people use the public sphere to form and disseminate public opinion in the form of demands to reject and withdraw from the Istanbul Convention. The intense lobbying efforts of the Turkish people in the public sphere show that they can influence and mobilize the state to protect family values ​​in Turkey, thus prompting the Turkish government to decide to leave the Istanbul Convention.